1)(x+2)(x-2)-x(x-6)=0
2)3x(4x+12x)-(6x-1)(6x+1)=11x
3)(x+7)(x-7)-(3x-1)(x+1)=4-2x^2

gulaydavay gulaydavay    1   22.01.2020 18:25    0

Ответы
Gfdsahjk Gfdsahjk  11.10.2020 02:29

1) (x+2)(x-2)-x(x-6)=0

раскроем скобки  

x2-2x+2x-4-x2+6x = 0

6x-4 = 0  

6x = 4

x  = \frac{4}{6}  

x  = \frac{2}{3}

2) 3x(4x+12x)-(6x-1)(6x+1)=11x

раскроем скобки  

12x2+36x2-36x2-6x+6x+1 = 11x

12x2-11x+1 = 0  

Вычислим дискриминант D

D = b2 - 4ac = ( – 11)2 – 4·12·( + 1) = 73

x1   =  11 + √ 73

              24

x2 =  11 – √ 73

             24

3)(x+7)(x-7)-(3x-1)(x+1)=4-2x2

раскроем скобки  

x2-7x+7x-49-3x2-3x+x+1 = 4-2x2

-2x-52 = 0  

2x+52 = 0

2x = -52

x = -26

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика